A arte da cibercultura mediando processos educativos no ensino fundamental - Gesteira, Rozane Suzart (2008)
This work is part of the line of research, educational processes and language of the course of Master in Education at the University of Passo Fundo, constitutes a reflection about cyberculture art as it mediates and permeates the educational processes of a public school, belonging to the town hall educational system, in the city of Marau, state of Rio Grande do Sul. The digital technologies have primordial importance in the current social context, due to its inserting, directly or indirectly, in our daily lives. In that sense, the digital inclusion should be part of the curriculum objectives that need to understand it as a means of mediating autonomy, expression and researching processes, around the technological phenomenon. Guided by a human conception of education, the digital inclusion assumes an educational dimension when it is unleashed from the consumerism of information, from the technical qualification and from the handling of equipments, in order to offer tools for the subject. In that sense, art promotes a more deepened reflection on the creative use of such equipments, divesting them from marketing objectives and addressing them for the local production, experimentation, and investigation on the different ways of expressing oneself